PENGARUH KUALITAS PELAYANAN DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH PADA PT.BANK RIAU KEPRI CABANG SIAK - Fandrifal, Rama (Eko dan Bisnis: Riau Economic and Business Review, 2016)
This study aims to determine the effect of service quality that consists of professionalism & skills, attitude & behavior, accessibility & flexibility, reliability & trustworthiness, service recovery, servicescape    on customer satisfaction  , the influence of customer satisfaction on customer loyalty, and the impact of service quality through customer satisfaction on customer loyalty. Research using the research object PT.Bank Riau Kepri branch Siak located in the city of Siak Sri Indrapura, as the object is always saving clients who transact savings over 3 years data were collected by distributing questionnaires to 100 respondents . Analysis tools using multiple linear regression analysis . The results showed that when the quality of service considered it will increase customer satisfaction, if customer satisfaction note it will increase customer loyalty and if the service quality through customer satisfaction , the customer will be considered more loyal. With increasingly improved service and result in increased customer satisfaction will make loyal customers using the products and services of PT . Bank Riau Kepri